Method for predicting geopolymer proportion and geopolymer-aggregate interface bonding performance based on molecular simulation

Through molecular dynamics simulation and interface model construction, the problem of difficult to evaluate the interaction between geopolymer and aggregate is solved, and the mechanical properties of geopolymer and interface bonding properties of aggregate are optimized, which reduces experimental costs and time. Provides guidance for actual engineering.

CN119446358AActive Publication Date: 2025-02-14TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411478603.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-14
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

The prior art is difficult to effectively evaluate the interaction between the dipolymer and aggregate, and traditional macroscopic experiments are difficult to optimize the mechanical properties and construction properties of the dipolymer, which is costly.

Method used

The influence of different raw material components on the performance of geopolymers was studied through molecular dynamics simulation, and a geopolymer-aggregate interface model was constructed to calculate interface interaction energy to guide raw material ratio and design.

Benefits of technology

In-depth analysis of geopolymer mechanical properties and aggregate interface bonding properties is achieved, which significantly reduces experimental costs and time, optimizes material properties, and provides guidance for aggregate selection in actual engineering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119446358A_ABST
    Figure CN119446358A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of geopolymer industrial materials, and particularly relates to a method for predicting geopolymer proportion and geopolymer-aggregate interface bonding performance based on molecular simulation. According to the method, geopolymer models with different calcium contents are constructed through molecular dynamics simulation, the mechanical properties of the geopolymer models are simulated, then simulation results are verified through experiments, the method can effectively predict the influence of the raw material ratio on the mechanical properties of the geopolymer, the time and cost required by the experiments are remarkably reduced, and the method is suitable for popularization and application. And an important reference is provided for subsequent design and optimization of geopolymer materials. Besides, interface models of the geopolymer, the coal gangue aggregate and the granite aggregate are constructed, the interface interaction between different types of aggregates and the geopolymer is explored on the molecular level, the combination degree of the geopolymer and the different aggregates is evaluated by calculating the interface interaction energy between the geopolymer and the different aggregates, and a splitting experiment is carried out for verification. And valuable guidance is provided for selection and application of aggregates in actual engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of resource utilization of industrial solid waste materials, and specifically relates to a method for predicting geopolymer proportion and geopolymer-aggregate interface bonding performance based on molecular simulation. Background Art

[0002] With the continuous growth of the global economy and the accelerated urbanization process, the demand for cement has increased dramatically. However, the high energy consumption and high emissions in the cement production process have become increasingly prominent, becoming a major challenge restricting sustainable development. Geopolymer, as an emerging green building material, is regarded as a substitute for traditional cement. It is mainly formed by a series of chemical reactions of natural minerals or industrial waste rich in silicate under the action of alkali activators. Its rise and application is not only a positive response to environmental protection needs, but also an important practice of the concept of resource recycling.

[0003] Geopolymers have the characteristics of high strength, durability, environmental protection and low cost, and are widely used in the fields of building materials, solid waste treatment and high temperature resistant materials. The traditional common raw materials for preparing geopolymers include metakaolin, circulating fluidized bed fly ash, fly ash, red mud, slag, silica fume, etc., but each raw material contains different types and contents of oxide components. If traditional experiments are used according to concrete curing specifications to explore the influence of the oxide content in each solid waste material on the performance of geopolymers, the experimental cycle is long and the cost is high.

[0004] In order to optimize the mechanical properties of geopolymers, improve construction performance and reduce costs, a certain amount of aggregate is usually added during the preparation process, which helps to improve the compressive strength, flexural strength and wear resistance of geopolymers, so that they can better meet the needs of various engineering structures. A large number of studies have shown that coal gangue and granite as aggregates have good environmental friendliness and economic benefits. At the same time, the addition of aggregates can also improve the fluidity and processability of geopolymers, facilitate construction operations, and improve construction efficiency. However, it is difficult to evaluate the interaction between aggregates and geopolymers using existing macroscopic experiments, so more sophisticated microscopic research and simulation methods are needed to deeply analyze this process.

[0005] Molecular dynamics simulation is a computer simulation method that studies the microscopic and macroscopic properties of a system by simulating the motion trajectories of atoms and molecules in the system. Based on the simulation results, the mechanical properties of different ratios of raw materials can be predicted, thereby optimizing the material design. The research of traditional building materials usually requires a lot of experimental verification, which is not only time-consuming and labor-intensive, but also costly. Molecular dynamics simulation can quickly conduct multiple simulation experiments through computer technology, and by comparing the simulation results under different conditions, the optimal solution can be selected, thereby greatly reducing the number and cost of conventional experiments.

[0006] The invention patent with application number CN202310410069.0 proposes a 137Cs wastewater treatment method based on molecular dynamics simulation. It uses molecular dynamics simulation to explore the process of geopolymer solidification of Cs atoms, but it is limited to the atomic level and has not been combined with practice. The invention patent with application number CN202410077340.8 proposes a method for constructing a molecular model of the interface between epoxy oligomer and phosphogypsum based on molecular dynamics simulation, but does not elaborate on how the model explains the mechanism between the material interfaces. At present, the research on the performance of geopolymers and their relationship with geopolymer aggregates is mostly limited to macroscopic experimental research, and there are few studies that use molecular dynamics simulation to explore their trends and guide experiments. Summary of the invention

[0007] In view of the shortcomings of the prior art, the present invention provides a method for predicting geopolymer ratio and geopolymer-aggregate interface bonding performance based on molecular simulation. The method studies the influence of different raw material component contents on geopolymer performance and the interaction between geopolymer and different types of aggregate interfaces through molecular dynamics simulation. Not only can the characteristics of geopolymer at the atomic level be deeply analyzed, but the simulation results can also be used to guide the raw material ratio and design in the experiment, thereby improving the experimental efficiency and optimizing the material performance.

[0008] In order to solve the above problems, the present invention first provides a method for optimizing the ratio of geopolymer raw materials based on molecular simulation, comprising the following steps:

[0009] (1) selecting the sialate-siloxo structural unit commonly used in geopolymers as oligomer small molecules for constructing the geopolymer model, filling a preset number of oligomer small molecules and alkali cations, wherein the charge number of the alkali cations is equal to the filling number of the oligomer small molecules;

[0010] (2) Perform energy minimization and melt annealing equilibrium processing on the constructed geopolymer model;

[0011] (3) Perform uniaxial compression simulation on the geopolymer model with different filling amounts after equilibrium, and record the compressive strength of the geopolymer model;

[0012] (4) Designing the ratio of geopolymer raw materials according to the number of filled alkali cations corresponding to the compressive strength.

[0013] Furthermore, the silicon-aluminum ratio of the sialate-siloxo structural unit is 2; the alkali cation is sodium ion and / or calcium ion, the filling number of the oligomer small molecule is 136, and the total charge number of the sodium ion and the calcium ion is 136;

[0014] The geopolymer raw materials include metakaolin, circulating fluidized bed fly ash and silica fume, and the amount of the circulating fluidized bed fly ash is proportional to the filling amount of the calcium ions in the geopolymer model.

[0015] Preferably, the geopolymer model component described in step (1) comprises 136 oligomer small molecules, 30 calcium ions, and 76 sodium ions.

[0016] Preferably, the geopolymer model component described in step (1) comprises 136 oligomer small molecules, 20 calcium ions, and 96 sodium ions.

[0017] Preferably, the geopolymer model component described in step (1) comprises 136 oligomer small molecules and 136 sodium ions.

[0018] The common way to build a model for molecular simulation is to use the Amorphous Cell module in the Materials Studio software. During the modeling process, click the Amorphous Cell option to output the number of small molecules and the set density. The software will automatically determine the size of the box based on the filled-in values. You can also set a target box size and density, and the software will calculate the number of structural units that need to be filled. The box containing all the small molecules can be regarded as a molecular model, such as Figure 1 The black wireframe in the Geopolymer diagram is this box, and the box plus all the small molecules inside it form a model.

[0019] The purpose of constructing a box in molecular simulation is to define the spatial scope and boundary conditions of the calculation. It is a basic operation of molecular simulation. By setting an appropriate box size, boundary effects can be avoided, thereby ensuring the accuracy and reliability of the simulation results.

[0020] The box size set in the present invention is The proposed density is 2g / cm 3 , then according to the set box size and density, the number of structures that need to be filled in this example can be obtained by inputting them into the software, which is 136.

[0021] Furthermore, the energy minimization process uses a conjugate gradient algorithm to make the geopolymer model reach the lowest energy state; the melt annealing equilibrium process includes balancing at a temperature of 300K for 50ps in the NVT ensemble, then balancing in the NVT ensemble at 1500K for 500ps, and cooling from 1500K to 300K at a rate of 5K / ps; then, balancing in the NPT ensemble and the NVT ensemble for 200ps respectively;

[0022] The operation steps of the uniaxial compression simulation are: applying uniaxial pressure to the model along the z-axis direction, and setting the strain rate during the compression process to a constant strain rate The pressure in the x and y directions is controlled to 0.

[0023] The present invention also provides a method for predicting geopolymer-aggregate interface bonding performance based on molecular simulation, comprising the following steps:

[0024] (1) Selecting a sialate-siloxo structural unit with a silicon-aluminum ratio of 2, which is common in geopolymers, as an oligomer small molecule for constructing a geopolymer model, and filling it with a preset number of oligomer small molecules and the same number of sodium ions;

[0025] (2) Select the mineral components with the highest content in coal gangue aggregate or granite aggregate to construct the aggregate model;

[0026] (3) combining the geopolymer model in step (1) and the aggregate model in step (2) to construct a geopolymer-aggregate interface model;

[0027] (4) Perform energy minimization and melt annealing equilibrium treatment on the constructed geopolymer-aggregate interface model;

[0028] (5) Calculate the interfacial interaction energy of the equilibrium geopolymer-aggregate interface model. The larger the absolute value of the interfacial interaction energy, the better the interfacial bonding performance.

[0029] Further in the step 2), the mineral component with the highest content selected from the coal gangue aggregate is kaolinite, and the mineral component with the highest content selected from the granite aggregate is quartz;

[0030] The geopolymer-aggregate interface model is constructed by combination using Build Layers in Materials Studio software;

[0031] The force field used in the molecular dynamics simulation is ReaxFF force field, and the time step is 0.25 fs; the molecular dynamics simulation equilibrium process is carried out in LAMMPS software.

[0032] Furthermore, the energy minimization process of the geopolymer-aggregate interface model is: using a conjugate gradient algorithm to perform geometric optimization on the geopolymer-aggregate model; the process of the melt annealing equilibrium process is: The following atoms are fixed and equilibrated at 300 K for 50 ps in the NVT ensemble. The system is heated to 1500 K for 500 ps equilibration and then cooled to 300 K at a rate of 5 K / ps. Finally, it is equilibrated in the NPT and NVT ensembles for 200 ps, ​​respectively.

[0033] Preferably, in the geopolymer-aggregate interface model, the geopolymer part includes 136 oligomer small molecules and 136 sodium ions, and the aggregate is kaolinite, which is the mineral component with the highest content in coal gangue aggregate.

[0034] Preferably, in the geopolymer-aggregate interface model, the geopolymer part includes 136 oligomer small molecules and 136 sodium ions, and the aggregate is quartz, the mineral component with the highest content in granite aggregate.

[0035] Furthermore, the calculation formula of the interfacial interaction energy of the geopolymer-aggregate interface model is:

[0036] E interface =EE geopolymer -E aggregate

[0037] In the formula, E interface is the interfacial interaction energy between geopolymer and aggregate, expressed in Kcal / mol;

[0038] E-total potential energy of geopolymer-aggregate interface model, in Kcal / mol;

[0039] E geopolymer is the potential energy of the geopolymer part, in Kcal / mol;

[0040] E aggregate It is the potential energy of the aggregate part, with the unit of Kcal / mol.

[0041] E interface are the values ​​obtained by calculation, E and E geopolymer , E aggregate It can be obtained by writing code, where E, E geopolymer , E aggregate The calculation process is as follows: Figure 3 The interface model shown on the right has geopolymer on the top and aggregate on the bottom. Determine the boundary between geopolymer and aggregate, calculate the total potential energy E of the interface model, and use the code to first delete the atoms of the geopolymer part (and the atoms above the boundary) in the interface model, and calculate the potential energy E of the remaining atoms, i.e., the aggregate part. aggregate Similarly, delete the atoms of the aggregate part (and the atoms below the dividing line) to obtain the potential energy E of the geopolymer part. geopolymer , the difference is E interface .

[0042] The present invention also conducts geopolymer model verification experiments, geopolymer ratio verification experiment preparation and testing, and the specific steps are as follows:

[0043] (1) Raw material processing: The metakaolin, circulating fluidized bed fly ash and silica fume were passed through a 0.075 mm square hole sieve, and the sieved materials were placed in an oven and dried to constant weight.

[0044] (2) Mixing of cementitious materials: Add kaolin, circulating fluidized bed fly ash and silica fume into a mixer and stir at a low speed for 1 minute to obtain a solid mixture. Then add the alkaline activator solution and stir at a high speed for 2 minutes.

[0045] (3) Curing: Pour the gelling slurry mixed in step (2) into a 40×40×40 mm mold, and use a scraper to flatten the surface of the mold. Cover the surface with plastic wrap, let it stand at room temperature for 24 hours, then demould and perform standard curing.

[0046] (4) Test: The samples cured for 7 days were subjected to infinite compressive strength test with a loading rate of 2.4 KN / s. The test results were recorded as the average of three times. The calculation process of the compressive strength of the test block cube is as follows:

[0047]

[0048] In the formula, f cc -compressive strength of cubic specimen (MPa); F-failure load of cubic specimen (N); A-pressure bearing area of ​​cubic specimen (mm 2 ).

[0049] The experimental preparation and testing characteristics of the geopolymer-aggregate interface bonding performance verification are as follows:

[0050] (1) Raw material processing: The metakaolin and silica fume were passed through a 0.075 mm square hole sieve, and the sieved materials were placed in an oven and dried to constant weight.

[0051] (2) Aggregate pretreatment: Cut the coal gangue aggregate and granite aggregate into 40×40×20 mm cuboids.

[0052] (3) Mixing cementitious materials: Add kaolin and silica fume into a mixer and stir at a low speed for 1 minute to obtain a solid mixture. Then add the alkaline activator solution and stir at a high speed for 2 minutes.

[0053] (4) Curing: Place the aggregate test block cut in step (2) on one side of a 40×40×40 mm mold, add the cementitious slurry mixed in step (3) to the other side, and use a scraper to flatten the mold surface. Cover the surface with plastic wrap, let it stand at room temperature for 24 h, then demould and perform standard curing.

[0054] (5) Test: Take the samples cured for 7 days and conduct splitting tensile test, with a loading rate of 1.0 KN / s. The test results are recorded as the average of three times. The splitting strength of the test block is calculated as follows:

[0055]

[0056] In the formula, f ts - splitting tensile strength (MPa); F- specimen failure load (N); A- specimen splitting surface area (mm 2 ).

[0057] Preferably, the components prepared in the geopolymer-aggregate interface bonding performance verification experiment include 70 parts of metakaolin and 30 parts of silica fume by weight, and the aggregate is coal gangue aggregate.

[0058] Preferably, the components prepared in the geopolymer-aggregate interface bonding performance verification experiment include 70 parts of metakaolin and 30 parts of silica fume by weight, and the aggregate is granite aggregate.

[0059] The present invention also provides a method for preparing geopolymer, which first adopts the above method to obtain an optimized geopolymer raw material ratio, and then mixes and cures the geopolymer raw materials; specifically comprises:

[0060] (1) Raw material processing: according to the ratio of geopolymer raw materials, kaolin, circulating fluidized bed fly ash and silica fume are passed through a 0.075 mm square hole sieve, and the sieved materials are placed in an oven and dried to constant weight;

[0061] (2) Mixing the gelled slurry: adding metakaolin, circulating fluidized bed fly ash and silica fume into a mixer and stirring for 1 minute to obtain a solid mixture, then adding an alkaline activator solution and stirring for 2 minutes to obtain a gelled slurry;

[0062] (3) Curing: Pour the gelled slurry mixed in step (2) into a mold, cover the surface with plastic wrap, and let it stand at room temperature for not less than 24 hours before demolding and performing standard curing to obtain a geopolymer.

[0063] Furthermore, the geopolymer comprises 40-70 parts of metakaolin, 0-30 parts of circulating fluidized bed fly ash, and 30 parts of silica fume by weight; wherein the total number of parts of the metakaolin, circulating fluidized bed fly ash and silica fume is 100 parts; and the mass ratio of the total number of parts of the metakaolin, circulating fluidized bed fly ash and silica fume to the alkaline activator solution is 100:40;

[0064] The composition of the metakaolin includes SiO2 51.72%, Al2O3 45.11%, CaO0.11%, Fe2O3 1.04%, K2O 0.78%, SO3 0.08% and TiO2 0.2% by mass fraction;

[0065] The components of the circulating fluidized bed fly ash include SiO2 34.41%, Al2O3 24.57%, CaO20.88%, MgO 1.26%, Fe2O3 5.15%, K2O 1.16%, SO3 9.6% and TiO2 1.17% by mass fraction;

[0066] The silica fume comprises SiO2 95.53%, Al2O3 0.46%, CaO 1.04%, Fe2O3 0.11%, MgO 0.34%, SO3 0.17% and TiO2 0.01% by mass fraction;

[0067] The alkaline activator solution is a mixed solution of sodium silicate solution and sodium hydroxide powder, wherein the sodium silicate solution has a SiO2 content of 26.2%, a Na2O content of 8.3%, a modulus of 3.2, a Baume degree of 40, a sodium hydroxide purity of 99%, and a modulus of 1.5.

[0068] Preferably, the geopolymer raw material ratio is as follows:

[0069] Preferably, the geopolymer validation experiment preparation components include 40 parts of metakaolin, 30 parts of circulating fluidized bed fly ash, and 30 parts of silica fume, by weight.

[0070] Preferably, the geopolymer validation experiment preparation components include 50 parts of metakaolin, 20 parts of circulating fluidized bed fly ash, and 30 parts of silica fume, by weight.

[0071] Preferably, the geopolymer verification experiment preparation components include 60 parts of metakaolin, 10 parts of circulating fluidized bed fly ash, and 30 parts of silica fume, by weight.

[0072] Preferably, the geopolymer validation experiment preparation components include 70 parts of metakaolin, 0 parts of circulating fluidized bed fly ash, and 30 parts of silica fume, by weight.

[0073] The standard curing temperature is 20±2°C and the humidity is ≥95%.

[0074] The present invention constructs geopolymer models with different calcium contents through molecular dynamics simulation, simulates their mechanical properties, and then verifies the simulation results through experiments. This method can effectively predict the influence of raw material ratio on the mechanical properties of geopolymer, significantly reduce the time and cost required for experiments, and provide an important reference for the design and optimization of subsequent geopolymer materials. In addition, the present invention also explores the interface interaction between different types of aggregates and geopolymers at the molecular level by constructing interface models of geopolymers and coal gangue aggregates and granite aggregates, evaluates the degree of combination between geopolymers and different aggregates by calculating the interface interaction energy between the geopolymers and different aggregates, and verifies it by splitting experiments, which provides valuable guidance for the selection and application of aggregates in actual engineering.

[0075] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0076] 1. The model of the present invention is simple to construct. By constructing a geopolymer model and a geopolymer-aggregate interface model, the microscopic properties of the material can be explored from the atomic level, and then the influence of the raw material ratio on the mechanical properties of the geopolymer can be reflected to a certain extent. The prediction results of molecular simulation can provide guidance for the design of the experiment. With the help of the simulation results, the content of circulating fluidized bed fly ash can be controlled in the experiment, reducing the blindness and trial and error costs of the experiment. At the same time, the degree of bonding between geopolymers and aggregates can be explored by adjusting different types of aggregates, so as to provide a certain reference for the selection of aggregate types in the experiment. The experimental results can also provide new research directions and ideas for molecular simulation. The two complement each other, so that the characteristics of the material can be better understood.

[0077] 2. The present invention utilizes computer simulation technology, which is simple to operate and has a short simulation cycle, greatly simplifying the problems of long traditional experimental cycles and high costs. It provides a new prediction and optimization approach for exploring the influence of raw material ratios on the compressive strength of geopolymers, and the simulation data has a good fit with the experiment.

[0078] 3. The use of molecular dynamics simulation can make up for the shortcomings of experiments to a large extent. For aspects that traditional experiments cannot cover, such as the characteristics and differentiation of aggregate structure, molecular dynamics simulation can intuitively and clearly reflect its characteristics, which has certain guiding significance for the types of aggregates in subsequent actual projects. BRIEF DESCRIPTION OF THE DRAWINGS

[0079] Figure 1 Schematic diagram of the process built for the geopolymer model.

[0080] Figure 2Schematic diagram of the constructed geopolymer model, wherein (a) is the geopolymer model constructed in Example 1, (b) is the geopolymer model constructed in Example 2, (c) is the geopolymer model constructed in Example 3, and (d) is the geopolymer model constructed in Example 4.

[0081] Figure 3 Schematic diagram of the process built for the geopolymer-aggregate model.

[0082] Figure 4 Schematic diagram of uniaxial compression simulation of geopolymer model.

[0083] Figure 5 Schematic diagram of the interface interaction energy composition of the geopolymer-aggregate model. DETAILED DESCRIPTION

[0084] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0085] Simulation Example 1

[0086] like Figure 1 As shown, the method for constructing a geopolymer model based on molecular dynamics simulation in the present invention is carried out in the following steps:

[0087] (1) Constructing geopolymer model: The sialate-siloxo structural unit with a silicon-aluminum ratio of 2, which is common in geopolymers, was selected as the oligomer small molecule for constructing geopolymers. 136 oligomer small molecules, 40 calcium ions, and 56 sodium ions were filled in the model according to the number, and the starting density was set to 2 g / cm 3 , and the initial geopolymer model is obtained. Among them, the oligomer small molecule is the sialate-siloxo structural unit, which is a silicate structural unit and an inorganic small molecule. The specific molecular structure is shown in Figure 1 Left picture.

[0088] (2) Equilibrium setting: First, the conjugate gradient algorithm is used to minimize the energy to ensure that the system reaches the lowest energy state. The melt annealing equilibrium process includes the model being balanced at 300K for 50 ps in the NVT ensemble to ensure the basic stability of the density. After that, the model is balanced in the NVT ensemble at 1500K for 500 ps and cooled from 1500K to 300K at a rate of 5K / ps. Subsequently, the model is balanced in the NPT ensemble and the NVT ensemble for 200 ps respectively.

[0089] (3) Compressive strength: The compressive strength of the geopolymer model is measured by applying uniaxial pressure to the model along the z-axis. The strain rate during compression is set to a constant engineering strain rate. The NPT ensemble was used at a temperature of 300 K, and the pressure in the x and y directions was controlled to be zero.

[0090] Simulation Example 2

[0091] The operation process is the same as that of simulation 1, except that 136 oligomer small molecules, 30 calcium ions, and 76 sodium ions are filled in according to the quantity when constructing the geopolymer model.

[0092] Simulation Example 3

[0093] The operation process is the same as that of simulation example 1, except that 136 oligomer small molecules, 20 calcium ions, and 96 sodium ions are filled in according to the quantity when constructing the geopolymer model.

[0094] Simulation Example 4

[0095] The operation process is the same as that of simulation example 1, except that 136 oligomer small molecules and 136 sodium ions are filled in according to the quantity when constructing the geopolymer model.

[0096] On the other hand, see Figure 3 The method for constructing a geopolymer-aggregate interface model based on molecular dynamics simulation of the present invention is carried out in the following steps:

[0097] Simulation Example 5

[0098] (1) Constructing geopolymer model: The sialate-siloxo structural unit with a silicon-aluminum ratio of 2, which is common in geopolymers, was selected as the oligomer small molecule for constructing geopolymers. 136 oligomer small molecules and 136 sodium ions were filled in the model according to the number, and the starting density was set to 2 g / cm 3 , and obtain the initial geopolymer model.

[0099] (2) Constructing the aggregate molecular model: Kaolinite, the mineral component with the highest content in coal gangue aggregate, was selected as the aggregate unit cell. The kaolinite unit cell was cut along the common crystal plane (001), and the aggregate unit cell was expanded to a size close to that of the geopolymer unit cell.

[0100] (3) Combined model: The geopolymer model constructed in step (1) and the aggregate model constructed in step (2) are combined using the Build Layer module in Materials Studio software to construct a geopolymer-gangue aggregate interface model.

[0101] (4) Equilibrium setting: First, energy minimization is performed and the geometry of the geopolymer-gangue aggregate model is optimized using the conjugate gradient algorithm to ensure that the system reaches the lowest energy state. The melt annealing equilibrium process includes: The following atoms were fixed to better explore the reaction at the interface of the composite material, and then balanced at 300K for 50ps in the NVT ensemble, and then the system was treated at 1500K for 500ps to accelerate the polymerization of the reaction, and then cooled at a rate of 5K / ps until the system temperature dropped to 300K. Finally, it was balanced in the NPT ensemble and NVT ensemble for 200ps respectively.

[0102] (5)Interface interaction energy: E interface =EE geopolymer -E aggregate

[0103] Where E interface -interfacial interaction energy between geopolymer and aggregate (Kcal / mol);

[0104] E - total energy of geopolymer-aggregate interface model (Kcal / mol);

[0105] E geopolymer - Potential energy of the geopolymer fraction (Kcal / mol);

[0106] E aggregate -Potential energy of the aggregate fraction (Kcal / mol).

[0107] Simulation Example 6

[0108] The simulation method is the same as that of Simulation Example 5, except that quartz, the mineral component with the highest content in granite aggregate, is selected as the aggregate unit cell when constructing the aggregate molecular model.

[0109] In addition to the molecular dynamics simulation, the present invention also conducted geopolymer strength and geopolymer-aggregate interface bonding strength verification experiments. The specific operation method of the geopolymer strength verification experiment is carried out according to the following steps:

[0110] Experimental Example 1

[0111] (1) Raw material processing: The metakaolin, circulating fluidized bed fly ash and silica fume were passed through a 0.075 mm square hole sieve, and the sieved materials were placed in an oven and dried to constant weight.

[0112] (2) Mixing cementitious materials: Add kaolin, circulating fluidized bed fly ash and silica fume into a mixer at a mass ratio of 40 parts, 30 parts and 30 parts, and stir at a low speed for 1 minute to obtain a solid mixture. Then add the alkaline activator solution and stir at a high speed for 2 minutes to obtain a cementitious slurry.

[0113] (3) Curing: Pour the gelling slurry mixed in step (2) into a 40×40×40 mm mold, and use a scraper to flatten the surface of the mold. Cover the surface with plastic wrap and let it stand at room temperature for 24 hours. After 24 hours, demold and perform standard curing.

[0114] (4) Test: The samples cured for 7 days were subjected to infinite compressive strength test with a loading rate of 2.4 kN / s. The test results were recorded as the average of three times. The calculation process of the compressive strength of the test block cube is as follows:

[0115]

[0116] In the formula, f cc - cubic specimen compressive strength (MPa); F- specimen failure load (N); A- specimen pressure bearing area (mm 2 ).

[0117] Experimental Example 2

[0118] The preparation method is the same as that in Example 1, except that the mass proportions of kaolin, circulating fluidized bed fly ash and silica fume are 50 parts, 20 parts and 30 parts respectively.

[0119] Experimental Example 3

[0120] The preparation method is the same as that in Example 1, except that the mass proportions of kaolin, circulating fluidized bed fly ash and silica fume are 60 parts, 10 parts and 30 parts respectively.

[0121] Experimental Example 4

[0122] The preparation method is the same as that in Example 1, except that the mass proportions of kaolin, circulating fluidized bed fly ash and silica fume are 70 parts, 0 parts and 30 parts respectively.

[0123] The specific operation method of the geopolymer-aggregate interface bond strength verification experiment is carried out according to the following steps:

[0124] Experimental Example 5

[0125] (1) Raw material processing: The metakaolin and silica fume were passed through a 0.075 mm square hole sieve, and the sieved materials were placed in an oven and dried to constant weight.

[0126] (2) Mixing of cementitious materials: Add kaolin and silica fume into a mixer and stir at a low speed for 1 minute to obtain a solid mixture. Then add the alkaline activator solution and stir at a high speed for 2 minutes.

[0127] (3) Aggregate processing: Cut the gangue aggregate into 40×40×20mm cuboids.

[0128] (4) Curing: Place the aggregate test block cut in step (3) on one side of a 40×40×40 mm mold, add the mixed cementitious slurry to the other side, and use a scraper to flatten the mold surface. Cover the surface with plastic wrap and let it stand at room temperature for 24 h. After 24 h, demould and perform standard curing.

[0129] (5) Test: The samples cured for 7 days were subjected to splitting tensile test with a loading rate of 1.0 KN / s. The test results were recorded as the average of three times. The calculation process of the compressive strength of the test block cube is as follows:

[0130] In the formula, f ts - splitting tensile strength (MPa); F- specimen failure load (N); A- specimen splitting surface area (mm 2 ).

[0131] Experimental Example 6

[0132] The preparation method is the same as that of Example 5, except that granite aggregate is used as the aggregate.

[0133] Analysis of results of a method based on molecular simulation to predict geopolymer mix ratio and geopolymer-aggregate interface bonding properties:

[0134] 1. Geopolymer molecular dynamics simulation design and analysis

[0135] Geopolymers were first proposed and studied in depth by J. Davidovits in 1978. Their unique three-dimensional network structure is generated by the polymerization reaction of many oligomer small molecules. Geopolymer structural oligomer small molecules can be divided into sialate structural units (Si / Al=1), sialate-siloxo structural units (Si / Al=2), and sialate-disiloxo structural units (Si / Al=3) according to the silicon-aluminum ratio. Therefore, the present invention selects sialate-siloxo structural units with a common silicon-aluminum ratio (atomic molar ratio) of 2 in geopolymers as oligomer small molecules for constructing geopolymers, controls the number of oligomer small molecules in each group of models to be constant, adjusts the ratio of calcium ions and sodium ions, and designs different geopolymer model components as shown in Table 1. In molecular dynamics simulation, the total charge of anions and cations must be equal. Therefore, in the molecular simulation setting, the number of sialate-siloxo structural units is firstly guaranteed to be constant, that is, the charge of anions is constant, and then the ratio of sodium ions to calcium ions is calculated so that the total charge of cations is also 136.

[0136] Table 1 Summary of components of geopolymer model

[0137]

[0138] The above four groups of balanced geopolymer models are respectively Figure 4 Uniaxial compression simulations were performed with the same simulation settings for each group, and the resulting compressive strengths are shown in Table 2.

[0139] Table 2 Summary of simulated uniaxial compression strength of geopolymers

[0140]

[0141] 2. Molecular dynamics simulation design and analysis of geopolymer-aggregate interface bonding performance

[0142] Two common aggregates, gangue and granite, were used in this simulation. However, due to their complex mineral composition, it is difficult to construct a model that fully displays their true complex state and properties at the molecular scale. Therefore, the mineral components with the highest content are usually selected to represent the aggregates to simplify the model and highlight their key features, so as to more accurately study their performance and behavior. Although this operation simplifies the complexity of the aggregates, it can still effectively reflect their key characteristics and interactions in the simulation. Therefore, kaolinite and quartz, the two mineral components with the highest content, are selected to represent the aggregates for gangue aggregates and granite aggregates, respectively. Both groups of geopolymers are filled with the same number of oligomer small molecules and sodium ions. The specific configuration is shown in Table 3.

[0143] Table 3 Summary of components of geopolymer-aggregate interface model

[0144]

[0145] Molecular dynamics simulations were performed on the above two groups of geopolymer-aggregate interface models, and the interfacial interaction energy between geopolymer and aggregate was calculated. The calculation results are summarized in Table 4.

[0146] Table 4 Interfacial interaction energy of geopolymer-aggregate interface model

[0147]

[0148] The magnitude of the interfacial interaction energy directly reflects the bonding strength between geopolymer and aggregate. This time, the interfacial interaction energy between geopolymer and coal gangue aggregate and granite aggregate was calculated by establishing the interfacial model between geopolymer and these two aggregates. The results are shown in Table 4. It can be found that the interfacial interaction energy of the two aggregates is negative, indicating that the geopolymer and these two aggregates are mutually attractive, and the absolute value of the interfacial interaction energy of granite is larger than that of coal gangue, indicating that the bonding degree between granite aggregate and geopolymer is better. Therefore, by simulating and calculating the interfacial interaction energy between geopolymer and aggregate, the bonding degree between different types of aggregates and geopolymer can be predicted, which provides a certain theoretical basis for the selection of aggregates in actual engineering.

[0149] 3. Geopolymer validation test design and analysis

[0150] In the geopolymer verification experiment, metakaolin (MK), circulating fluidized bed fly ash (CFBFA) and silica fume (SF) were selected as raw materials for preparing geopolymers. The alkaline activator was a mixed solution of sodium silicate solution and sodium hydroxide powder. Among them, metakaolin was the most commonly used raw material for preparing geopolymers. Circulating fluidized bed fly ash was a by-product of circulating fluidized bed boilers in power plants. Its application in building materials can effectively reduce waste landfill and realize resource recycling. In view of the fact that the geopolymer model in this molecular dynamics simulation selected oligomer small molecules with a silicon-aluminum ratio of 2, the silicon-aluminum ratio of 2 must be met in the verification experiment. A higher proportion of silica fume was added to supplement the silicon source. The proportion of oxides in the geopolymer raw materials is shown in Table 5.

[0151] Table 5 Ratio of raw material oxides

[0152]

[0153] It can be found from Table 5 that the calcium oxide content in kaolin and silica fume is extremely small and can be ignored. Therefore, in this experiment, circulating fluidized bed fly ash can be regarded as the only source of calcium content. On this basis, the proportions of the three raw materials of kaolin, circulating fluidized bed fly ash and silica fume are adjusted according to the molecular dynamics simulation parameter settings. The specific proportions of the verification experiment are shown in Table 6.

[0154] Table 6 Summary of geopolymer model components

[0155]

[0156] According to the four experimental mix proportions designed in Table 6, geopolymer slurry test blocks were prepared, and the geopolymer test blocks obtained from the experiment were subjected to standard curing. The infinite compressive strength was tested after 7 days of curing. The test results are shown in Table 7.

[0157] Table 7 Summary of 7d compressive strength of experimental geopolymers

[0158]

[0159] Combining the molecular dynamics simulation (Table 2) with the experimental results (Table 7), it can be found that the compressive strength change trends of the simulation and experiment in the four groups of ratios proposed this time are consistent. With the increase of the circulating fluidized bed fly ash content (the number of calcium ions), the compressive strength increases accordingly, indicating that the calcium content has a certain reinforcing effect on improving the mechanical strength of the geopolymer, verifying that the experimental and molecular dynamics simulation results are in good agreement. Therefore, the molecular dynamics simulation of the present invention can reflect the mechanical properties of different raw material ratios to a certain extent. In addition, the parameters corresponding to the molecular dynamics model can be adjusted by calculating the specific silicon-aluminum ratio and calcium-silicon ratio in the experiment, so as to predict the mechanical properties, optimize the experimental ratio, and save time cycle and experimental cost to a great extent.

[0160] 4. Design and analysis of geopolymer-aggregate interface bond verification test

[0161] In the geopolymer-aggregate interface bonding degree verification experiment, in order to better explore the influence of aggregate type on the geopolymer-aggregate interface bonding performance, the geopolymer ratio was controlled to be the same in this example, and ratio 4 in Table 6 was selected as the geopolymer ratio in the geopolymer-aggregate interface verification experiment. The samples cured for 7 days were taken for splitting tensile test, and the test results are shown in Table 8.

[0162] Table 8 Splitting tensile strength of geopolymer-aggregate specimens

[0163]

[0164] During the splitting tensile test, it can be observed that the cracks extend along the interface between the geopolymer and the aggregate, and eventually fail at the interface. Since the main components of granite aggregate and gangue aggregate are quartz and kaolinite, respectively, the strength of granite aggregate is generally higher than that of gangue aggregate, and higher aggregate strength helps to improve the overall strength of the composite material. By comparing the interface interaction energy and splitting tensile strength results of the geopolymer-aggregate interface model in Table 4 and Table 8, it can be found that the simulated interface interaction energy and splitting tensile strength test results both show that the granite aggregate has certain advantages in terms of bonding performance with the geopolymer, indicating that the geopolymer-aggregate interface model constructed in the present invention is also scientifically reasonable and has important guiding value for practical research.

[0165] It is undeniable that both molecular simulation and experiment have certain limitations. Molecular simulation cannot completely simulate the real state of experimental raw materials, and experiments may be limited by test conditions and other factors to produce errors. However, the prediction results of molecular simulation can provide guidance for the design of experiments. Just as in this example, the raw material ratio and aggregate type are both key factors affecting the performance of geopolymers. By adjusting the content of calcium ions in the model, it is found that the calcium content has a certain positive effect on the compressive strength of geopolymers. Therefore, with the help of the results obtained by simulation, the content of circulating fluidized bed fly ash can be controlled in the experiment to reduce the blindness and trial and error cost of the experiment. At the same time, the degree of bonding between geopolymers and aggregates can also be explored by adjusting different types of aggregates, so as to provide a certain reference for the selection of aggregate types in the experiment. The experimental results can also provide new research directions and ideas for molecular simulation. The two complement each other, so that the characteristics of the material can be better understood. The present invention uses molecular dynamics simulation technology, and the present invention can predict the strength of geopolymers under different raw material ratios and evaluate the degree of interfacial bonding between geopolymers and different types of aggregates. This method can provide a certain reference basis for the selection of raw materials and performance optimization in the design and application of geopolymer materials.

[0166] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for optimizing the ratio of geopolymer raw materials based on molecular simulation, characterized in that: Includes the following steps: (1) selecting the sialate-siloxo structural unit of the geopolymer as the oligomer small molecule for constructing the geopolymer model, filling a preset number of oligomer small molecules and alkali cations, wherein the charge number of the alkali cation is equal to the filling number of the oligomer small molecules; (2) Perform energy minimization and melt annealing equilibrium processing on the constructed geopolymer model; (3) Perform uniaxial compression simulation on the geopolymer model with different filling amounts after equilibrium, and record the compressive strength of the geopolymer model; (4) Designing the ratio of geopolymer raw materials according to the number of filled alkali cations corresponding to the compressive strength.

2. The method according to claim 1, characterized in that The alkali cation is a sodium ion and / or a calcium ion, the filling number of the oligomer small molecule is 136, and the total charge number of the sodium ion and the calcium ion is 136; The geopolymer raw materials include metakaolin, circulating fluidized bed fly ash and silica fume, and the amount of the circulating fluidized bed fly ash is proportional to the filling amount of the calcium ions in the geopolymer model.

3. The method according to claim 1, characterized in that The energy minimization process uses a conjugate gradient algorithm to make the geopolymer model reach the lowest energy state; the melt annealing equilibrium process includes balancing at a temperature of 300K for 50ps in the NVT ensemble, then balancing in the NVT ensemble at 1500K for 500ps, and cooling from 1500K to 300K at a rate of 5K / ps; then, balancing in the NPT ensemble and the NVT ensemble for 200ps respectively; The operation steps of the uniaxial compression simulation are: applying uniaxial pressure to the model along the z-axis direction, and setting the strain rate during the compression process to a constant strain rate The pressure in the x and y directions is controlled to 0.

4. A method for evaluating the bonding performance of geopolymer-aggregate interface based on molecular simulation, characterized in that: The following steps are involved: (1) Selecting the sialate-siloxo structural unit of the geopolymer as the oligomer small molecule for constructing the geopolymer model, filling a preset number of oligomer small molecules and the same number of sodium ions; (2) Select the mineral components with the highest content in coal gangue aggregate or granite aggregate to construct the aggregate model; (3) combining the geopolymer model in step (1) and the aggregate model in step (2) to construct a geopolymer-aggregate interface model; (4) Perform energy minimization and melt annealing equilibrium treatment on the constructed geopolymer-aggregate interface model; (5) Calculate the interfacial interaction energy of the equilibrium geopolymer-aggregate interface model. The larger the absolute value of the interfacial interaction energy, the better the interfacial bonding performance.

5. The evaluation method according to claim 4, characterized in that: In the step 2), the mineral component with the highest content selected from the coal gangue aggregate is kaolinite, and the mineral component with the highest content selected from the granite aggregate is quartz; The geopolymer-aggregate interface model is constructed by combination using Build Layers in Materials Studio software; The energy minimization process and melt annealing equilibrium process were both performed in LAMMPS software, and the force field selected was the ReaxFF force field with a time step of 0.25 fs.

6. The evaluation method according to claim 4, characterized in that: The energy minimization process of the geopolymer-aggregate interface model is: using a conjugate gradient algorithm to perform geometric optimization on the geopolymer-aggregate model; The process of melt annealing equilibrium treatment is: The following atoms are fixed and equilibrated at 300 K for 50 ps in the NVT ensemble. The system is heated to 1500 K for 500 ps equilibration and then cooled to 300 K at a rate of 5 K / ps. Finally, it is equilibrated in the NPT and NVT ensembles for 200 ps, ​​respectively.

7. The evaluation method according to claim 4, characterized in that: In the step 5), the calculation formula of the interfacial interaction energy of the geopolymer-aggregate interface model is: AND interface =EE geopolymer -AND aggregate In the formula, E interface is the interfacial interaction energy between geopolymer and aggregate, expressed in Kcal / mol; E is the total potential energy of the geopolymer-aggregate interface model, in Kcal / mol; E geopolymer is the potential energy of the geopolymer part, in Kcal / mol; E aggregate It is the potential energy of the aggregate part, with the unit of Kcal / mol.

8. A method for preparing a geopolymer, characterized in that: Firstly, the optimized geopolymer raw material ratio is obtained by the method described in any one of claims 1 to 3, and then the geopolymer raw materials are mixed and cured; specifically comprising: (1) Raw material processing: according to the ratio of geopolymer raw materials, kaolin, circulating fluidized bed fly ash and silica fume are passed through a 0.075 mm square hole sieve, and the sieved materials are placed in an oven and dried to constant weight; (2) Mixing the gelled slurry: adding metakaolin, circulating fluidized bed fly ash and silica fume into a mixer and stirring for 1 minute to obtain a solid mixture, then adding an alkaline activator solution and stirring for 2 minutes to obtain a gelled slurry; (3) Curing: Pour the gelled slurry mixed in step (2) into a mold, cover the surface with plastic wrap, and let it stand at room temperature for not less than 24 hours before demolding and performing standard curing to obtain a geopolymer.

9. The preparation method according to claim 8, characterized in that: The geopolymer comprises 40-70 parts of metakaolin, 0-30 parts of circulating fluidized bed fly ash, and 30 parts of silica fume by weight; wherein the total of the parts of the metakaolin, circulating fluidized bed fly ash and silica fume is 100 parts; the mass ratio of the total of the parts of the metakaolin, circulating fluidized bed fly ash and silica fume to the alkaline activator solution is 100:40; The composition of the metakaolin includes SiO2 51.72%, Al2O3 45.11%, CaO0.11%, Fe2O3 1.04%, K2O 0.78%, SO3 0.08% and TiO2 0.2% by mass fraction; The components of the circulating fluidized bed fly ash include SiO2 34.41%, Al2O3 24.57%, CaO20.88%, MgO 1.26%, Fe2O3 5.15%, K2O 1.16%, SO3 9.6% and TiO2 1.17% by mass fraction; The silica fume comprises SiO2 95.53%, Al2O3 0.46%, CaO 1.04%, Fe2O3 0.11%, MgO 0.34%, SO3 0.17% and TiO2 0.01% by mass fraction; The alkaline activator is a mixed solution of sodium silicate solution and sodium hydroxide powder, wherein the sodium silicate solution contains 26.2% SiO2, 8.3% Na2O, a modulus of 3.2, a Baume degree of 40, and a sodium hydroxide purity of 99%, wherein the modulus of the prepared alkaline activator mixed solution is 1.5; The standard curing temperature is 20°C ± 2°C and the humidity is ≥ 95%.

Citation Information

Patent Citations

  • Molecular model construction method of epoxy oligomer and ardealite interface based on molecular dynamics simulation

    CN117935977A

  • Evaluation method and system of anti-salt property of copolymer based on molecular simulation

    CN110021370A

  • Geopolymer wrapped aggregate and preparation method thereof

    CN112876149A

  • Evaluation method for low-temperature crack resistance of recycled asphalt mixture

    CN113555067A

  • Preparation method of garbage incineration fly ash geopolymer concrete

    CN114735976A